TRAINING TODAY'S INDIVIDUAL FOR TOMORROW'S INDIVIDUAL'S PERFORMANCE. LIFELONG LEARNING - Florentin Remus MOGONEA (Universitaria Publishing House, Craiova, 2020)
The contemporary world is characterized by a rapid and unpredictable evolution of science and technology, generating a significant movement of ideas, inventions and discoveries, an exponential growth of information and cutting-edge technologies. These have as a consequence the digitalisation of the society, the restructuring and the renewal of some multidisciplinary epistemological approaches, from all sectors of the social life. Contemporary society is facing limited resources of raw materials and energy, population growth, widening the gap between rich and poor countries, the steady deterioration of the environment, and interethnic conflicts. The solution to this crisis is the education reform, which will cause profound transformations in relation to the specificities of each country, a new education policy to increase its quality and imprint the prospective character. Through structure, objectives and content, education must constantly meet the requirements of the evolution of national and international reality. The meanings and efficiency of the educational act are given by the the adaptation and selfregulation capacity of education, compared to the more numerous challenges of the social space. Our paper aims to demonstrate the importance of lifelong learning, deepening and capitalising on it, after the period of compulsory schooling. Tomorrow's human education is no longer reduced to what the school transfers; it results from the harmonious combination of the three forms of education throughout life. This means that the training of today's individual, through education, will meet the demands of the tomorrow's knowledge society.